Предмет: Математика,
автор: dolbik22823
![y = \tan(3x) + \frac{1}{x} \: \: \: \: \: \: y {}^{1} = y = \tan(3x) + \frac{1}{x} \: \: \: \: \: \: y {}^{1} =](https://tex.z-dn.net/?f=y+%3D++%5Ctan%283x%29++%2B++%5Cfrac%7B1%7D%7Bx%7D++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+y+%7B%7D%5E%7B1%7D++%3D+)
dolbik22823:
да...
Ответы
Автор ответа:
1
Ответ: y'=3/cos²(3*x)-1/x².
Пошаговое объяснение:
y'=[tg(3*x)]'+(x⁻¹)'=1/[cos²(3*x)]*(3*x)'+(-1)*x⁻²=3/cos²(3*x)-1/x².
Похожие вопросы
Предмет: Геометрия,
автор: maiboroda1907
Предмет: Физика,
автор: annakanafocka
Предмет: Алгебра,
автор: pirimovairma69
Предмет: Обществознание,
автор: Anastasiasuperclass
Предмет: Математика,
автор: Димабро2006